Astenia, dolor y sufrimiento - Gónzalez Barón, Manuel; Ordóñez, Amalio; Lacasta, María Antonia (Psicooncología, 2004)
Introduction: The asthenia is a frequent symptom in the oncological patients who have important repercussions on their quality of life. In spite of its prevalence and relevance, some experts recognize that the great ignorance of this symptom exists. On the other hand the patients do not express the importance that stops they has the asthenia sensation, since they consider it inevitable. This fact is left patent in a study that compared the relative importance that each oncologist gave to the asthenia and the pain, with that it gave the patient him. Objective: To evaluate that symptom pain or asthenia worries to the oncological patients more and how can be helped to alleviate the suffering them that these symptoms can produce to him. Method: One has evaluated 187 oncological patients, in chemotherapy treatment, in the Service of Medical Oncology of the La Paz Hospital, of Madrid; on its preoccupations, the subjective perception of suffering and if there is something helps them to alleviate its suffering. Results: The 81 of the patients refers that there are different aspects that worry to them, like ill being, the family, future, pain and fatigue. The subjective perception of suffering is in EVA of 0-3 for 41% and the fatigue in EVA of 4- 7 in a 37% of the people worried about these symptoms. Also a 68% make some strategy to control the fatigue and 84% to control the pain. 62% of the patients worried about the pain and 57% of which is worried about the fatigue consider that it would be possible to be helped them to confront these symptoms.